Increasing Port Service Fees in The Sangihe Archipelago Regency: The Performance of The Department of Transportation - Christine Makawimbang; Joyce J Rares; Fanley N Pangemanan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The purpose of this study is to identify and examine the Department of Transportation's performance in increasing port service fees in the Sangihe Islands Regency. This study employs a qualitative descriptive research design. Primary and secondary data were used. The following people were interviewed: the Head of the Sangihe Islands Regency Transportation Service; the Head of the Sea Transportation, Port, Shipping, and Shipping Safety Section; the Head of the Program, Finance, and Reporting Section; Transportation Service Staff; and Port Service Users. The organizational theory of Agus Dwiyanto was applied by the researchers in this study, which took 3 (three) indicators. The study's findings show that there has been a failure to meet the target for transportation service fees because the Covid-19 Pandemic will occur in 2021, the community is still dissatisfied with the current Pananru Crossing Port infrastructure facilities, and the provision of false data from these services must be supported by research. It has not been improved in terms of supervision, particularly at Nusantara Tahuna Port, where there are no policemen watching clients who purchase boat tickets in addition to port entrance tickets. In terms of community unhappiness with the present infrastructure at the Pananaru Ferry Port, they complain to the high payment of fees, but the infrastructure facilities they use, as well as the service quality mechanism at the port, are not commensurate to what they pay for. This refers to the timing of invoicing and payment.